Commemorating Colonialism in a Post-Colonial World - Robert ALDRICH (E-REA)
Colonialists erected monuments, statues and other edifices to commemorate empire-building. Since the era of decolonisation, the construction of lieux de mémoire has continued, though now with commemoration of anti-colonialist nationalism and independence movements as well. Yet recent efforts show the paradoxes and challenges in trying to monumentalise colonialism and opposition to it. Examples of monuments to King Leopold of the Belgians, Henry Morton Stanley and Pierre Savorgnan de Brazza are used to illustrate post-colonial monument-building and its implication for the history and memory of overseas empires.